Osteoporosis Knowledge, Health Beliefs, and Calcium Intake among Malaysian Chinese Adults in Perak: A Cross-sectional Study - Ru, Thean Hui; Ab Kadir, Nurul Aimi; Mohd Shahrin, Fatin Izzaty (Makara Journal of Health Research, 2026)
Background: The Malaysian Chinese population records the highest national prevalence of osteoporotic hip fractures. This study investigated the relationships between osteoporosis knowledge, health beliefs, and calcium intake among Malaysian Chinese adults. Methods: A cross-sectional study was conducted among 205 Malaysian Chinese adults in Kampar, Perak, using the adapted Osteoporosis Prevention and Awareness Tool (OPAAT), Osteoporosis Health Belief Scale (OHBS), and a 30-item Food Frequency Questionnaire (FFQ). Results: Participants demonstrated low osteoporosis knowledge (6.84 ± 2.92), with low perceived susceptibility (14.87 ± 5.00), moderate perceived seriousness (17.81 ± 5.20), and barriers to calcium intake (15.61 ± 4.15), and high perceived benefits (22.73 ± 3.75) and health motivation (21.26 ± 3.84). The mean daily calcium intake was 530 ± 353.2 mg/day, with only 12% of participants achieving adequate intake. Knowledge of osteoporosis was significantly correlated with almost all health belief domains. Several statistically significant correlations were observed among the OHBS domains, and calcium intake was correlated with age (r = 0.181), osteoporosis knowledge (r = 0.141), perceived benefits (r = 0.177), perceived barriers (r = −0.240), and health motivation (r = 0.176). Conclusion: Strategies that improve osteoporosis awareness, strengthen health motivation, and reduce practical dietary barriers may support healthier calcium-intake behaviors among Malaysian Chinese adults.